Cover Image, Volume 74, Issue 5. Issue 5 (26th March 2018) - Van Horn, Christopher R; Moretti, Marcelo L; Robertson, Renae R; Segobye, Kabelo; Weller, Stephen C; Young, Bryan G; Johnson, William G; Schulz, Burkhard; Green, Amanda C; Jeffery, Taylor; Lespérance, Mackenzie A; Tardif, François J; et al.
Abstract : The cover image, by Christopher R Van Horn et al., is based on the Research Article Glyphosate resistance in Ambrosia trifida: Part 1. Novel rapid cell death response to glyphosate, DOI:10.1002/ps.4567 . Glyphosate‐susceptible (top) and ‐resistant (bottom) giant ragweed 2 (left) and 21 (right) days after glyphosate treatment. Abstract : The cover image, by Christopher R Van Horn et al., is based on the Research Article Glyphosate resistance in Ambrosia trifida: Part 1. Novel rapid cell death response to glyphosate, DOI:10.1002/ps.4567 . Glyphosate‐susceptible (top) and ‐resistant (bottom) giant ragweed 2 (left) and 21 (right) days after glyphosate treatment.